The Benefits of Removing Dirty Blood with Traditional Cupping Treatment - Amiruddin, Muhammad; Syafitri, Layla Intan; Rabbani, Afif; Muthmainnah, Aisya Kayla; Salsabila, Ainun Tusamma (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 2 (2022): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR), 2022)
In daily life, Muslims are ordered to behave by the teachings in the Al-Quran and the sunnah of the Prophet Muhammad, including regarding health. In the world of health, it is known that alternative medicine in the style of Rasulullah SAW is known as At-Thibb Al-Nabawi; one example is cupping therapy. The purpose of preparing this paper is to master the meaning of cupping, the procedures for carrying out cupping, and knowing the urgency and virtues of cupping. The research method used is a literature study. Cupping is the oldest traditional medicine method in the world, believed to have existed since 3000 BC. It aims to remove blood contaminated with toxins resulting from metabolism through the skin's surface by using a tube or glass placed on the skin's surface as a place to collect the dirty blood. There are five types of cupping: dry cupping, wet cupping, sliding cupping, fire cupping, and synergy cupping. Cupping features include pain relief, increasing blood circulation, lowering blood pressure, overcoming cardiovascular disease, lowering cholesterol, treating diabetes mellitus, and many more.